Multidiszciplináris elektronikus tananyag készítése, használata mechanika témakörben – egy tehetséggondozó szakkör terve - Pipics, János (Kultúratudományi Szemle, 2024)
Creation and use of multidisciplinary, electronic teaching materials in the field of mechanics - a plan for a talent development course My 2023 study on multidisciplinary digital learning materials in mechanics examined how to strengthen cross-curricular themes in physics, especially for study groups. I created a Multidisciplinary Physics Project for Talented Students, a method of talent development I use as a primary school teacher. The 18-week course can be divided into three different parts. First is introduction and multidisciplinary lessons. On these occasions, the group summarises the laws learned in physics lessons, and after that, they examine everyday phenomena, artworks, inventions, and historical sources via physics and use their knowledge to understand how the learned facts appear in other fields and examples. The second part is inquiry-based learning, in which students choose one theme from the multidisciplinary stage and then research it individually. On the last of these lessons, they present their results to each other and their teachers (jury) on Talent Day. The last stage is for rewards, for example, school trips. In my study, based on that former one, I introduced the elements of these projects, the modules, the suggested themes and cross-curricular connections and the programme’s usage. In addition, I wrote about the first module (Modul A) that has already been constructed.